The role of the Polish diaspora in Argentina in the context of preserving and transforming Polish national identity facing contemporary migration challenges (Estudios Sociales, 2025)
The article analyzes the migration process of Polish-origin population to Argentina, focusing on the issue of preserving national identity in the context of integration with the local society. This text presents the history of this migration, from the first waves of immigration in the 19th century to contemporary challenges such as globalization and the changing forms of identity among the Polish diaspora. To achieve this goal, the role of Polish community institutions in Argentina, such as schools, churches, and cultural organizations that supported the preservation of Polish heritage, was explored. This production shows how the Polish population in Argentina has successfully integrated into a multicultural society without losing their national identity.
Keywords: Migration; Polish diaspora; polish community in Argentina; polish migration in Argentina; national identity; polish organization in Argentina